The Impact of Computer- Based Video-games Devices on the Children’s Health - Jamel, Melad Faiq; Shafiq, Wesam Saadoon; Abdul-wahid, Salwa Sh (Diyala Journal of Medicine, 2019)
Background: Computer video games require great attention and focus, the more exposure to interactive media, the more exposure to challenges that will recommend players to play better and gain more intelligence. Objective: To identify the health effects on children under five years using computer –based video games by electronic devices including mobile phone,computer and ipad. Patients and Methods: A cross-sectional study was conducted in Al-Batul teaching hospital, for the period from the first of September /2016 to the 15th January \2017. The study sample included (100) of children aged 1-5 years, attending the hospital for the purpose of treatment, or accompanying their mothers. The Data collected through a questionnaire designed by the researchers. Results: Revealed that there was statistical significance relationship between electronic devices and mother's educational level which is more in mother with college educational level. There is no significant relationship between children using electronic devices and there residence. High significant statistical relation -ship between children using electronic device and health problems (p -value equal to <0.001), mainly shown for children using electronic device and decrease appetite, hyperactivity, lack of sleep and with attention defect. Conclusion:Computer-based vedio games associated with behavioral changes like hyperactivity, attention deficit, lack of sleep and loss of appetite.